Transgender nation - MacKenzie, Gordene O. (Bowling Green State Univ. Popular Press, 1994)
This book asks what transsexual ideology, individual transsexuals, transgenderists and cross-dressers and the representations of transgenderists in the popular media reveal about contemporary U.S. gender attitudes.